Agile Governance Pemerintah Kota Bogor dalam Pembangunan Transportasi Publik Biskita untuk Mengatasi Kemacetan - Yusril Hawari , Alhilal; Suwaryo, Utang; Sri Kartini, Dede (Jurnal Ilmiah Administrasi Publik, 2024)
Transportation essential to people's lives because it drives the economic, social, and development. Bogor has the nickname of a million angkots because angkots fill the roads and leading cause of congestion. Biskita is the answer to the congestion problem. This research uses descriptive qualitative methods with the theory of Agile Governance. Data collection is done through interviews and documentation. Determination of informants with purposive, data validation with data triangulation, data analysis using data reduction, data presentation, and conclusion drawing. The results showed Agile Governance of the Bogor City Government has been successful, as seen from the fulfillment of five existing indicators, namely Business Operations with the existence of local regulations, Moderator Effect with the procurement of BISKITA, Governance Capabilities with the implementation of SOPs on BISKITA, Agile Capabilities with education and training, Value Delivery with plans to develop BISKITA. An increase in the Impact of Environmental Factors is needed, which has not been fulfilled due to decreased public interest in using BISKITA. The conclusion is the performance of the Bogor City Government in developing Biskita can be improved. Seeing that the level of public participation in using Biskita is still low, the number of angkot has not decreased, service counters at bus stops have not yet operated, congestion still occurs in Bogor City, two bus stop corridors are still not operating from a total of 6 planned bus stop corridors.